Antibacterial Activity of Extract Combination Gel of Cherry Leaf (Muntingia calabura L.) and Beluntas Leaf (Pluchea indica L.) againts Staphylococcus aureus - Nanik Sulistyani; Tegar Prasetya Budi; Aprilia Kusbandari (Sanata Dharma University, 2023)
Staphylococcus aureus (S. aureus) infection is a critical problem, in health care because there are S. aureus found that are resistant to antibiotics. Some alternative treatments of infection include herbal plants such as cherry (Muntingia calabura L.) and beluntas (Pluchea indica L.) leaves since they contain antibacterial compounds. Cherry and beluntas leaves are formulated in gel form since they are easy to use. This study aims to determine the physical properties, microbial contamination and antibacterial activity of the gel preparation. Combination of cherry leaf extract and beluntas leaf extract with a concentration ratio of 2.5: 0.5 was formulated in gel preparations with concentrations of 3%, 6% and 12%. The gel was later tested for physical properties including tests for organoleptic, pH, spreadity diameter, adhesity, and viscosity. The gel was also tested for the number of yeasts and antibacterial activity by the agar well diffusion method. The results were analyzed with SPSS 20.0.0 with One-way ANOVA. The results of the physical properties test for the gel preparation for viscosity were: (5666.18; 6369.23; and 8540.11) cps, the pH value was (7.58; 7.11; and 6.45), the scattering diameter was ( 6.16; 5.88; and 5.00) cm, the value of adhesity (74.66; 80.99; and 98.18) seconds, respectively. The test results of the yeast mold number obtained 3x102 CFU/mL. The results of the inhibition zone diameters were (6.00; 7.90; and 10.00) mm, respectively. Based on these research findings, the difference in extract concentration affects the physical properties of the gel. The gel formula with a 12% concentration has physical properties reaching the requirements, meets the requirements for the value of yeast mold numbers, and provides the most optimal antibacterial activity.